Lithium-selective composite materials based on TiO2 and MnO2 - Rozhdestvenska, Lyudmyla; Chaban, Mariya; Belyakov, Volodymyr (My University, 2016)
Ion-exchange materials based on titanium dioxide-manganese dioxide composite were synthesized by template method. It was proved that sorption characteristics of the obtained materials depend of rate of heat treatment during the synthesis. Higher temperatures promote agglomeration of sorbent and decrease in its kinetic characteristics. But more lithium-selective sorption centers are formed and the selectivity of sorption increases.
Keywords: titanium dioxide; manganese dioxide; ion exchange selectivity; діоксид титану; діоксид мангану; іонообмінна селективніть